FAKTOR YANG MEMPENGARUHI MAHASISWA SEBAGAI PEKERJA SEKS KOMERSIAL DI KOTA SEMARANG - Nella Vallen Ika Puspita (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Modern times bring positive and negative impacts on people's social life, such as the rise of free sex. It is not an open secret, the campus as a place for printing intellectual and moral generations is now a place for the development of free sex practices. The purpose of this study is to find out the factors behind students becoming commercial sex workers. This research is a qualitative descriptive research using case study method. The sampling technique used is snowboll sampling, with the main informants being students as female sex workers or female sex workers in the city of Semarang. Data collection techniques used in this study were in-depth interviews, indirect observation and document analysis. The validity of the data in this study includes source triangulation, method triangulation, theory triangulation and researcher triangulation. Data analysis in this study used a pattern matchmaking analysis model, namely data reduction, data presentation and data analysis that formed a pattern that could reveal the factors that influenced students as commercial sex workers. Several factors that influence students to become sex workers include economic factors, family background, campus environment and customers